Asosiasi Antara Promosi Program Keluarga Berencana dan Perilaku Penggunaan Alat Kontrasepsi - Abigail Pasaribu; Lamtiur H. Tampubolon (Jurnal Perkotaan, 2015)
The growth of the birth rate in Indonesia is not comparable with the availability of labour force and it has an impact on national economic conditions. Therefore, the BKKBN (National Family Planning Coordinating Board) is very active to conduct various forms of promotion of the Family Planning (KB) in order to reduce the birth rate and to achieve a prosperous family. This study seeks to examine the association between the promotion of family planning programs with the use of contraceptive method among the parish of the church which is characterized by a certain ethnic group, in West Jakarta. By using simple random sampling, the questionnaire was distributed to 123 respondents of the 20-44 -year old. This study used simple linear regression analysis and the result showed that there was a very strong relationship between the promotion of family planning programs and the behavior of the use of contraceptive method.